Genesis Exploration of White Clays Deposited in Thimi Area of Kathmandu Valley - Dhakal, Madhusudan; Duwal, Nirjan; Adhikari, Narendra Mani; Joshi, Susan; Bhattarai, Jagadeesh (Journal of Nepal Chemical Society, 2021)
The geological genesis of the Thimi-Sanothimi white clay deposits of Kathmandu Valley was explored employing mineralogical and chemical analyses in this research. For the study, two sample specimens of the clay having two types of particle size, i.e., about < 63 µm (bulk) and < 2 µm (fine), were separated with the help of standard sieve mesh which further modified using high-temperature heat, and 1 M HCl and 1 M KCl solution treatments. For the most part, both the clay fractions constituted of 2:1 type of vermiculite and mica (mainly of K-mica type) clay minerals with different feldspars and quartz phases as clay admixtures from the results of the mineralogical phase analysis. The chemical constituents of the clay particles with < 63 µm, < 2 µm, and the HCl-treated sample specimens confirmed the existence of a high quantity of SiO2 with comparatively low Al2O3 which indicates the presence of fewer amounts of the vermiculite and mica minerals comparatively with feldspars and quart admixtures in the analyzed white clay samples. Moreover, the clay sample contained a considerable quantity of Fe2O3 and MgO chemicals which are not favorable raw material constituents for good quality porcelains and white-wares products without refining and chemical-modifications. The present work could be the first step to explore its potentiality in various industrial sectors like table-ware, sanitary-ware, brick and tile ceramics, paper and pulp, petrochemical, pharmaceutical including environmental pollution controlling agents in Nepal.